1990
DOI: 10.1046/j.1537-2995.1990.30891020331.x
|View full text |Cite
|
Sign up to set email alerts
|

Red cell autoantibodies, multiple immunoglobulin classes, and autoimmune hemolysis

Abstract: The effects and interrelationships of multiple immunoglobulin coating (i.e., increased red cell [RBC]-bound IgM and/or IgA in addition to IgG) were investigated in 404 patients with warm-reactive RBC autoantibodies on 590 occasions. Multiple immunoglobulins were detected by enzyme-linked direct antiglobulin tests in 218 samples (37%), but in only 87 (15%) by agglutination methods. Differences in populations were examined by chi-square, with p less than 0.005 being required for significance because of the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 25 publications
5
28
0
Order By: Relevance
“…Severely anemic patients are usually symptomatic and require RBC transfusions [18]. Usually, crossmatchcompatible RBCs cannot be found and "least incompatible" units will be transfused [5,14,15,16,17,20].…”
Section: Discussionmentioning
confidence: 99%
“…Severely anemic patients are usually symptomatic and require RBC transfusions [18]. Usually, crossmatchcompatible RBCs cannot be found and "least incompatible" units will be transfused [5,14,15,16,17,20].…”
Section: Discussionmentioning
confidence: 99%
“…1). As the patient samples were selected on the basis of a posi tive direct antiglobulin test for IgG, the presence of raised IgA levels in some of them was not surprising in view of the known occurrence of multiple immunoglobulin coat ing of red cells in autoimmune haemolysis; it has been reported that about 14% of patients with increased amounts of cell-bound IgG also have increased amounts of cell-bound IgA and, in some cases, IgM [ 1,3]. It is perti nent that the seven highest IgA values obtained here (116-4,500 molecules per cell) were on the specimens which had shown increased amounts of IgA on the routine test, 2 patients having autoimmune haemolytic anaemia, 3 myelodysplastic syndrome, 1 chronic lymphocytic leu kaemia and 1 rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with autoimmune haemolytic disease, the relationship between the immunoproteins bound to the red cells and the degree of in vivo haemolysis is a complex one [1][2][3]. To elucidate this relationship further, a satis factory quantitative method for determining the levels of the different immunoproteins would be invaluable.…”
Section: Introductionmentioning
confidence: 99%
“…These include hereditary hemolytic anemias, paroxysmal nocturnal hemoglobinuria, microangiopathic hemolytic disorders, aplastic anemia, megaloblastic anemia, and anemias associated with many other disorders. The following hemolytic anemias are sometimes difficult to differentiate from AIHA of the warm type by serological testing: drug-induced toxic or immune hemolysis, hemolytic transfusion reactions (particularly those associated with transfusion-induced autoantibodies of RBCs), pregnancy associated autoantibodies to RBCs, paroxysmal cold hemoglobinuria, AIHA of cold type, particularly those related to antibodies with high temperature amplitudes [35][36][37], and most importantly all types of immune hemolytic anemias related to transient lymphocyte syndrome secondary to solid organ or bone marrow transplantation [38,39].…”
Section: Warm Antibody Autoimmune Hemolytic Anemiamentioning
confidence: 99%